A novel metal coordination enabled in carboxylated alginic acid for effective fluoride removal. (15th March 2015) - Pandi, Kalimuthu; Viswanathan, Natrayasamy
Highlights: Synthesis of carboxylated alginic acid (CAA) and metal coordinated CAA (M-CAA). First time, CAA and M-CAA was utilized for fluoride removal. M-CAA possess higher defluoridation capacity than CAA. In field study, M-CAA reduce fluoride concentration below the tolerance limit. M-CAA is a low cost, eco-friendly and biodegradable sorbent. Abstract: This article enlightens the synthesis of carboxylated alginic acid (CAA) and metal ions coordinated CAA (M-CAA) for defluoridation studies in batch mode. The oxidation of alginic acid (AA) with KMnO4 gives CAA and the metal coordination was enabled in CAA by using high valence metal ions viz., La 3+ (La-CAA) and Zr 4+ (Zr-CAA). The synthesized materials Zr-CAA, La-CAA and CAA possess the defluoridation capacities (DCs) of 4064, 3137 and 880 mgF − /kg respectively. An enhanced DC was observed for metal-coordinated CAA (M-CAA) than CAA. The defluoridation experiments were carried with numerous influencing parameters like contact time, pH and competitor anions for optimization. The characterization of materials was carried out using FTIR, EDAX and SEM analysis. The sorption data was fitted with various isotherms and kinetic models. The values of thermodynamic parameters indicate the nature of fluoride removal is spontaneous and endothermic. At field conditions, M-CAA reduce the fluoride concentration below the tolerance limit.